(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The Direct Method is a natural and immersive approach to foreign language teaching that emphasizes the exclusive use of the target language in instruction. This study explores its theoretical foundations, practical application in the classroom, and effectiveness in enhancing communicative competence among learners. Through qualitative review and analysis of prior implementations, the study highlights both the advantages and limitations of the method. Findings reveal that while the Direct Method fosters oral fluency and listening comprehension, it requires skilled instructors and small class sizes to be truly effective. The discussion provides implications for incorporating the Direct Method into modern language pedagogy.